Inside Windows Server 2003 - Boswell, William (Addison-Wesley, 2003)
Inside Windows .NET Server contains comprehensive information on deploying, managing, and troubleshooting systems using both Windows .NET and its predecessor. Readers get the in-depth, practical knowledge they need to master the hundreds of complex and often frustrating features found in Windows .NET Server. Inside Windows .NET Server is structured around a production deployment of Windows .NET in a global enterprise. Each chapter contains a lively feature description followed by extensively illustrated procedures for setting up and managing each service. All along the way, Boswell includes proven advice for improving stability, performance, and security. Readers of Boswell's Inside Windows 2000 Server declared it to be the best resource on the market. Inside Windows .NET Server improves coverage of existing features while expanding the scope to include the new features and improvements that make Windows .NET a must-have upgrade.